D-Dimer Is Associated With Coronary Microvascular Dysfunction in Patients With Non-obstructive Coronary Artery Disease and Preserved Ejection Fraction - Lin, Yan; Hu, Xiangming; Wang, Weimian; Yu, Bingyan; Zhou, Langping; Zhou, Yingling; Li, Guang; Dong, Haojian (Frontiers in Cardiovascular Medicine, 2022)
Background Coronary microvascular dysfunction (CMVD), an important etiology of ischemic heart disease, has been widely studied. D-dimer is a simple indicator of microthrombosis and inflammation. However, whether an increase in D-dimer is related to CMVD is still unclear. Materials and Methods This retrospective study consecutively enrolled patients with myocardial ischemia and excluded those with obstructive coronary artery. D-dimer was measured at admission and the TIMI myocardial perfusion grade (TMPG) was used to distinguish CMVD. Patients were divided into the two groups according to whether the D-dimer was elevated (>500 ng/ml). Logistic models and restricted cubic splines were used to explore the relationship between elevated D-dimer and CMVD. Results A total of 377 patients were eventually enrolled in this study. Of these, 94 (24.9%) patients with CMVD had older age and higher D-dimer levels than those without CMVD. After full adjustment for other potential clinical risk factors, patients with high D-dimer levels (>500 ng/ml) had a 1.89-times (95% CI: 1.09–3.27) higher risk of CMVD than patients with low D-dimer levels. A non-linear relationship was found between concentrations of D-dimer and CMVD. With increased D-dimer level, the incidence of CMVD increased and then remained at a high level. Stratified analysis was performed and showed similar results. Conclusion Elevated D-dimer level is associated with the incidence of CMVD and potentially serves as a simple biomarker to facilitate the diagnosis of CMVD for patients with angina.